Dermacoccus sp. isolated from a brain abscess in a 4-year-old child - Ivaska Lauri; Alyazidi Raidan; Hoang Linda; Goldfar David M. (Elsevier B.V., 2022)
Dermacoccus spp. have rarely been reported as human pathogens. We describe a case of a 4-year-old boywith congenital heart disease who was diagnosed with a brain abscess. The abscess was drained and thesample grew Streptococcus intermedius, Aggregatibacter aphrophilus and Dermacoccus sp..Dermacoccus grew after 5 days of incubation and the patient was treated with meropenem.